PENERAPAN LITERASI PADA ANAK USIA DINI MELALUI MEDIA VISUAL - syafe'i, Muhammad; Estiningsih, Nining; Yuliastri, Nur Adiyah (STAI Darul Kamal Darul Kamal NW Kembang Kerang, 2024)
This research aims to: (1) Understand the Implementation of Early Childhood Literacy Through Visual Media at BA Aisyiyah Tlingsing, Cawas, Klaten. The approach used in this research is qualitative. The subjects of this research consisted of students of BA Aisyiyah Tlingsing, Cawas, Klaten. This research data was collected through interviews, observation and document analysis. This research data was analyzed using interactive qualitative analysis techniques including data collection, data reduction, data presentation, and drawing conclusions. The results of the research show that the implementation of Early Childhood Literacy Activities at BA Aisyiyah Tlingsing, Cawas, Klaten includes strategic aspects of reading books, developing text-rich environments in schools, literacy support charts, functional charts for communication in the classroom, text-rich charts made by teachers and students, student writing displays, word walls, classroom reading corners. Methods for implementing literacy activities at BA Aisyiyah Tlingsing, Cawas, Klaten include reading story books, looking for letters, syllables and words, singing, playing with my name, making letters or words using materials around the child. Keywords: literacy, visual media, flash cards